La protezione della vita umana “al tramonto”, tra legge e libertà di coscienza (Stato, Chiese e pluralismo confessionale, 2023)
The protection of human life “at sunset”, between law and freedom of conscienceABSTRACT: The paper proposes to suggest to the Italian legislator, which must further intervene on the matter of the end of life, and has also been solicited by the Constitutional Court, some methods that can allow a synthesis between the different conflicting ethical and political positions that animate the debate on life and human dignity. It is considered appropriate that the law does not favor the ad libitum exercise of the freedom of self-determination in end-of-life choices, and that the most suitable category for orienting the balance between equality and freedom of self-determination according to dignity must be solidarity, which makes a person that is all the more alive and human the more he is inserted into a civil and supportive society.SOMMARIO: 1. Il biodiritto tra posizioni etiche e politiche contrastanti - 2. Il consenso-informato e le disposizioni anticipate di trattamento - 3. Il suicidio assistito: un eccessivo diritto giurisprudenziale? - 4. La sterile contrapposizione tra autodeterminazione solipsistica e solidarietà sociale - 5. Le cure palliative - 6. La laicità procedurale nella giuridificazione delle scelte di fine-vita - 7. L’esperienza del diritto ecclesiastico a servizio del biodiritto.